RAYMOND WESTERLING’S REPRESENTATION OF DE TURK CHARACTER IN THE FILM “DE OOST” (2020) - Balfas, Orchida; Nugraha, Fajar Muhammad (International Review of Humanities Studies, 2023)
"De Oost" is a film directed by Jim Taihuttu, a Netherlandsman of Ambon descent, which tells the story of the Westerling Tragedy. Its launch sparked controversy from former Netherlands East Indies veterans to Raymond Westerling's daughter because it was considered to distort facts and not fit Westerling's description. This controversy raises the problem of how Jim Taihuttu represents Westerling through the character de Turk. This research is intended so that readers can assess Jim Taihuttu's depiction of Westerling through the character de Turk and determine the suitability of the film with reality. The research method used is qualitative using the note-taking technique, by applying identity theory by Erick Erikson (1968) to find out the director's background and representation theory by Stuart Hall (1995) to examine Westerling's representation in films. This research resulted in the answer that Jim Taihuttu was quite objective in depicting Westerling by representing nicknames, life, and cruelty, but also balanced by de Turk's friendly nature towards his soldiers. The representation of the character de Turk by Jim Taihuttu's "De Oost" indirectly illustrates how the new generation of Netherlands views Raymond Westerling in a more objective way.